Effect of air-particle-abrasion protocols on surface roughness and early biofilm formation of zirconia - Macedo, Vanessa Cruz; Pereira, Priscilla Cristoforides [UNESP]; de Queiroz, José Renato Cavalvanti; de Oliveira Dal Piva, Amanda Maria [UNESP]; Moura, Dayanne Monielle Duarte [UNESP]; Tangof, Rubens Nisie; Bottino, Marco Antonio [UNESP]; de Assunção e Souza, Rodrigo Othávio (My University, 2020)
Purpose: The air-particle-abrasion on zirconia in the gingival area of connectors and pontics in fixed partial dentures appears to increase fracture resistance. This study evaluated 'in situ' biofilm formation on the zirconia surface after different air-particle-abrasion protocols. Materials and Methods: Ninety sintered blocks (5 x 5 x 2 mm) of yttrium partially stabilised zirconia (Y-TZP) were obtained and randomised among nine groups according to the factors 'type of particle' (Alumina 50 and 110 μm; Cojet and Rocatec) and 'pressure' (2.5 and 3.5 bar) used for sandblasting for 10 s. The surface roughness (Ra/ Rz) was measured before and after sandblasting. For the in-situ analyses, custom-made removable intraoral devices n = 10 with one sample of each group attached to the buccal area were used by volunteers for 8 h at night. The specimens were analysed under confocal microscopy to quantify both biovolume and thickness of the initial biofilm formed. One-way analysis of variance (ANOVA) and Dunnett's tests were performed (5%). Results: The roughness values ranged from 0.05 to 0.39 μm for Ra and from 0.35 to 2.11 μm for Rz, p = 0.00. Mean biofilm thickness ranged from 0.06 and 0.54 μm (p = 0.005), while the biovolume values were between 0.02 and 0.61 μm3/μm2 (p = 0.002). Values statistically significant for biofilm thickness and biovolume were found in groups sandblasted with Rocatec using 3.5 bar. Conclusion: In order to increase the fracture resistance of zirconia fixed partial dentures (FPDs), the air particle abrasion of zirconia with SiO2 (110 μm/3.5 bar), in the gingival area of connectors and pontics, should be avoided.
Keywords: Blasting; Scanning electron microscopy; Surface roughness; Zirconia